The Mechanisms and Kinetics of Radical Scavenging Activity of Edaravone: A Computational Insight - Yen, Tran Thi; Manh, Tran Duc; Mechler, Adam; Son, Nguyen Hong; Uyen, Huynh Thi Diem; Bich, Huynh Ngoc; Quan, Vo Van (VNU Journal of Science: Natural Sciences and Technology; Vol 38 No 3DO - 10.25073/2588-1140/vnunst.5373, 2022)
Edaravone ( EDV , 3-methyl-1-phenyl-2-pyrazolin-5-one) is a neuroprotective drug that has been used to treat acute stroke caused by cerebral thrombosis and embolism. Studies showed that  EDV  could be used to treat diseases related to oxidizing agents; however, the activity has not been fully studied yet. In this study, the free radical scavenging activity of  EDV  was investigated by thermodynamic and kinetic calculations. The results showed that  EDV  exhibited good HOO • radical scavenging activity in an aqueous medium at pH = 7.40 ( k overall (HOO) = 8.58´107   M -1 s -1 ) through the electron transfer mechanism of the anion state. In contrast, this activity was insignificant in non-polar environments.  EDV  also exhibited excellent antiradical activity against HO · , CH 3 O · , CH 3 OO · , O 2 ·- , NO 2 , SO 4 ·- , N 3 · and DPPH radicals in the aqueous solution. Thus, it appears to suggest that  EDV  is a promising radical scavenger in polar environments.